MELACARE Nurse-led follow-up after early-stage melanoma: protocol and feasibility - Sara M. Hansen; Christoffer Johansen; Magnus P.B. Obinah; Nadine A. Kasparian; Peter Genter; Pernille E. Bidstrup; Lisbet R. Hölmich (Acta Oncologica)
Background and purpose: We developed the Melacare nurse-led intervention, which combines education in skin self-examination as a resource-conscious approach to detecting recurrence and management of fear of cancer recurrence in patients treated for melanoma. This publication presents the Melacare study protocol and evaluates the feasibility and acceptability of Melacare prior to a larger randomised controlled trial.